ROLUL COMPETENŢELOR PARENTALE PRIVIND EFICIENŢA EDUCAŢIEI DE GEN ÎN CADRUL FAMILIEI - USM ADMIN (Moldova State University, 2007)
The article reflects an applicational study regarding the consequence of parents competences for the gender educa- tion in family. The efficiency of gender education will be in dependence of the parental competences, gender behaviors and that educational influence which the parents must apply in concordance with children peculiarities and gender.